Explanation of Water Indices and Criteria in the Urban Landscape in Order to Improve the Quality of Urban Environments - Zeynab khaleghi; Farah Habib; Hossein Zabihi (تحقیقات کاربردی علوم جغرافیایی)
Water as one of the most essential natural elements of landscape and consequently urban landscape from yesterday till today has had a great impact on the formation and effectiveness of urban spaces and its various effects have always stimulated human tendency towards beauty. It should be noted that the existential values ​​of water are not merely aesthetic, rather it goes back to the deepest and innermost part of nature. Such a stimulus has led human beings to recognize different aspects of water, including sensory and perceptual, visual, semantic, functional, physical-aesthetic, environmental, psychological, social, and temporal and this knowledge has provided the backdrop for a variety of water-based designs in the urban landscape. The main purpose of the present study is to identify all the features and existential values ​​of water and their proper application in the urban landscape. In other words, the explanation of a specific pattern including major water criteria and indicators in the urban landscape has been considered to improve the quality of the landscape in urban environments. The research method is applied and the type of study is descriptive-analytical and data collection is based on the study of library resources and content analysis of text. The results of the research indicate that by applying all the existing dimensions and values ​​of water element in the urban landscape, the quality of urban spaces can be improved. The use of water criteria and indicators in the urban landscape in a coherent and integrated manner requires a compiled pattern that is presented in the end in a tabular form.